2017
DOI: 10.7324/japs.2017.70718
|View full text |Cite
|
Sign up to set email alerts
|

Papaya fruits extracts enhance the antioxidant capacity and modulate the genotoxicity and oxidative stress in the kidney of rats fed ochratoxin A-contaminated diet

Abstract: Ochratoxin A (OTA) is a mycotoxin widespread contaminates food and has potent nephrotoxicity. The present study aimed to determine total phenolics and DPPH radical scavenging activity for water and ethanolic extracts (WE and EE) of papaya fruits and evaluation of the protective role of these extracts against OTA-induced oxidative damage and nephrotoxicity in rats. Sixty male Sprague-Dawley rats were divided into six groups and treated for 21 days as follow: the control group, OTA-treated group (3 mg/kg diet), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…DNA disruption and oxidative stress play an important role in numerous cancers and pathological disorders, including carcinogenesis and aging (Soltani et al 2009;Jacobsen-Pereira et al 2018). Numerous experiments have shown that plant-derived natural compounds demonstrate defensive behaviors against genotoxicity caused by oxidative stress (Plazar et al 2008;El-Nekeety et al 2017;Rahmouni et al 2018). Fruits and vegetables include many types of phytochemicals with antioxidant, anti-mutagenic and anticarcinogenic properties (Arora et al 2002;Shahidi & Ambigaipalan 2015;Janet al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…DNA disruption and oxidative stress play an important role in numerous cancers and pathological disorders, including carcinogenesis and aging (Soltani et al 2009;Jacobsen-Pereira et al 2018). Numerous experiments have shown that plant-derived natural compounds demonstrate defensive behaviors against genotoxicity caused by oxidative stress (Plazar et al 2008;El-Nekeety et al 2017;Rahmouni et al 2018). Fruits and vegetables include many types of phytochemicals with antioxidant, anti-mutagenic and anticarcinogenic properties (Arora et al 2002;Shahidi & Ambigaipalan 2015;Janet al 2018).…”
Section: Introductionmentioning
confidence: 99%